Protecting Your Eyes from Pesticide Exposure - Frederick M. Fishel (EDIS)
PI-165, a 4-page illustrated fact sheet by Frederick Fishel, describes various types of personal protective equipment (PPE) appropriate for providing eye protection as required on pesticide labels. Includes additional information. Published by the UF Department of Agronomy, July 2008.